Passive Immunotherapy Protects against Enteric Invasion and Lethal Sepsis in a Murine Model of Gastrointestinal Anthrax - Bruce Huang; Tao Xie; David Rotstein; Hui Fang; David M. Frucht (Toxins, 2015)
The principal portal for anthrax infection in natural animal outbreaks is the digestive tract. Enteric exposure to anthrax, which is difficult to detect or prevent in a timely manner, could be exploited as an act of terror through contamination of human or animal food. Our group has developed a novel animal model of gastrointestinal (GI) anthrax for evaluation of disease pathogenesis and experimental therapeutics, utilizing vegetative Bacillus anthracis (Sterne strain) administered to A/J mice (a complement-deficient strain) by oral gavage. We hypothesized that a humanized recombinant monoclonal antibody (mAb) * that neutralizes the protective antigen (PA) component of B. anthracis lethal toxin (LT) and edema toxin (ET) could be an effective treatment. Although the efficacy of this anti-anthrax PA mAb has been shown in animal models of inhalational anthrax, its activity in GI infection had not yet been ascertained. We hereby demonstrate that passive immunotherapy with anti-anthrax PA mAb, administered at the same time as gastrointestinal exposure to B. anthracis, prevents lethal sepsis in nearly all cases (>90%), while a delay of up to forty-eight hours in treatment still greatly reduces mortality following exposure (65%). Moreover, passive immunotherapy protects against enteric invasion, associated mucosal injury and subsequent dissemination by gastrointestinal B. anthracis, indicating that it acts to prevent the initial stages of infection. * Expired raxibacumab being cycled off the Strategic National Stockpile; biological activity confirmed by in vitro assay.